Is the design of dietary based studies enough with a quantitative description? - San Mauro Martin, Ismael; Bermejo de las Heras, Sara; Garicano Vilar, Elena (Progress in Nutrition, 2018)
Objective: A proper diet, from a macronutrients quantitative point of view, does not imply it is qualitatively correct. We demonstrate that quantitative dietary advice may be qualitatively deficient. Design and setting: A search for suitable recommendations of macronutrients contribution to total energy intake was performed. Two similar quantitative (15-25% proteins, 45-60% carbohydrates and 20-35% fat) but qualitatively different weekly menus were designed using DIAL software. Menu A provides more fibre, MUFAs, vitamins, minerals and minor components of the diet than menu B and PUFAs/SFA index is higher. In menu B, SFA, cholesterol, glucose and sucrose levels are higher. Results: Menu A has better qualitative contribution of carbohydrates, fat, vitamins and minerals; it is better adjusted to the dietary reference values, and provides more phytochemicals components. It also has more fibre and less simple sugar. Menu B provides plenty of fructose mainly from soft drinks. Conclusions: Diet may be deficient if only planned taking in consideration the quantitative aspect. All of this can generate wrong study analyses and conclusions.